Pharmacokinetics of Tildipirosin in Plasma, Milk, and Somatic Cells Following Intravenous, Intramuscular, and Subcutaneous Administration in Dairy Goats - Juan Sebastián Galecio; Pedro Marín; Verónica Hernandis; María Botía; Elisa Escudero (MDPI AG, 2022)
Tildipirosin is a macrolide currently authorized for treating respiratory diseases in cattle and swine. The disposition kinetics of tildipirosin in plasma, milk, and somatic cells were investigated in dairy goats. Tildipirosin was administered at a single dose of 2 mg/kg by intravenous (IV) and 4 mg/kg by intramuscular (IM) and subcutaneous (SC) routes. Concentrations of tildipirosin were determined by an HPLC method with UV detection. Pharmacokinetic parameters were estimated by non-compartmental analysis. Muscle damage, cardiotoxicity, and inflammation were evaluated. After IV administration, the apparent volume of distribution in the steady state was 7.2 L/kg and clearance 0.64 L/h/kg. Plasma and milk half-lives were 6.2 and 58.3 h, respectively, indicating nine times longer persistence of tildipirosin in milk than in plasma. Moreover, if somatic cells are considered, persistence and exposure measured by the area under concentration-time curve (AUC) significantly exceeded those obtained in plasma. Similarly, longer half-lives in whole milk and somatic cells compared to plasma were observed after IM and SC administration. No adverse effects were observed. In brief, tildipirosin should be reserved for cases where other suitable antibiotics have been unsuccessful, discarding milk production of treated animals for at least 45 days or treating goats at the dry-off period.